Fiscal policy experiments - Ilias Georgakopoulos (Economics and Econometrics Research Institute (EERI), 2019)
This paper investigates the macroeconomic implications of alternative tax regimes. For this purpose, a one-sector general equilibrium model is constructed in which heterogeneous agents differ in productivity and holdings of capital in the sense of incurring transaction costs for participating in the capital market. A Cobb-Douglas production function is employed that can capture the capital-skill complementarity effect and the difference in productivities of the skilled and unskilled workers. With regards to fiscal policy experiments, this paper examines tax structures where a permanent reduction in each of the three main tax instruments namely, consumption, labour and capital income tax is compensated by a permanent increase in one of the remaining two policy instruments such that the government budget constraint is tax revenue neutral. The government levies taxes on consumption, labour income and capital income in order to finance its only activity, government consumption. Next, the model economy is calibrated to the Greek economy to reflect the great ratios over 1960:1-2005:4 and then, it studies the long-run, welfare and transitional effects of the undertaken analysis. The sensitivity analysis shows that the quantitative and qualitative findings are quite robust.
Keywords: E24; E32; E62; 330; General equilibrium model; optimal taxation; business cycle